Hybrid Nanostructures for High‐Sensitivity Luminescence Nanothermometry in the Second Biological Window. (14th July 2015) - Cerón, Elizabeth Navarro; Ortgies, Dirk H.; del Rosal, Blanca; Ren, Fuqiang; Benayas, Antonio; Vetrone, Fiorenzo; Ma, Dongling; Sanz‐Rodríguez, Francisco; Solé, José García; Jaque, Daniel; Rodríguez, Emma Martín
<x xml:space="preserve">Abstract</x> Hybrid nanostructures containing neodymium‐doped nanoparticles and infrared‐emitting quantum dots constitute highly sensitive luminescent thermometers operating in the second biological window. They demonstrate that accurate subtissue fluorescence thermal sensing is possible.